Basic Medical Laboratory Services as an Effort to Detect Metabolic Syndrome in Anduonohu Sub-District, Kendari City - Ratih Feraritra Danu Atmaja; Theosobia Grace; Tuty Yuniarty; Julianti Isma Sari (Lambung Mangkurat, 2023)
Metabolic syndrome is an accumulation of metabolic disorders that can increase the risk of cardiovascular-related diseases and type 2 diabetes mellitus. Metabolic syndrome is characterized by central obesity, hyperglycemia, hypertriglyceridemia, hypertension and decreased of HDL level. Community basically already knows each parameter separately but still rarely knows about the condition if these parameters occur together as metabolic syndrome. This study aimed to socialize as well as brought laboratory services closer to detect metabolic syndrome. This activity was carried out on 50 residents of the Anduonohu Village, Poasia District, Kendari City. Laboratory services performed include measurement of body mass index (BMI), waist circumference, blood pressure, blood glucose and blood cholesterol. Detection of metabolic syndrome using the definition of the International Diabetes Foundation 2009 by assessing the parameters of central obesity, blood pressure and glucose levels showed that 48% of the participants had metabolic syndrome